2022
DOI: 10.1002/pc.26600
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the dynamic behavior of composite gradient double‐arrow auxetic structure under local impact load

Abstract: Based on the design concept of functionally graded materials, the composite gradient double-arrow auxetic structures were designed and fabricated. The thickness of core layers demonstrates an increasing trend for positive gradient structure, while a decreasing trend for negative gradient structure. The thickness of core layers keeps constant for homogeneous structure. The dynamic response and failure modes of the double-arrow auxetic structure with different gradient distributions of wall thickness were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The researchers observed that the distribution of thickness gradients in the multi-layered composite wall, with layers of different thicknesses, had a significant influence on the dynamic response and failure modes of the structure. 25 Meymand et al studied the collapse behavior of cylindrical aluminum energy absorbers that were partially or fully hybridized with glass fibers and epoxy resin during lowvelocity impact. The researchers found that the fully hybridized samples exhibited the highest energy absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers observed that the distribution of thickness gradients in the multi-layered composite wall, with layers of different thicknesses, had a significant influence on the dynamic response and failure modes of the structure. 25 Meymand et al studied the collapse behavior of cylindrical aluminum energy absorbers that were partially or fully hybridized with glass fibers and epoxy resin during lowvelocity impact. The researchers found that the fully hybridized samples exhibited the highest energy absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al examined the response and failure modes of multi‐layered composite laminates with varying thicknesses during high‐velocity impact tests. The researchers observed that the distribution of thickness gradients in the multi‐layered composite wall, with layers of different thicknesses, had a significant influence on the dynamic response and failure modes of the structure 25 …”
Section: Introductionmentioning
confidence: 99%
“…With these enhanced properties, auxetic composites are prominent in various applications such as protective equipment and energy absorption materials 6–9 . Since Milton et al 10 indicated the possibility of manufacturing of auxetic composite laminates with the Poisson's ratio (PR) of −1, many researches have been focused on the development of auxetic composites and the studies of their energy absorption ability and impact resistance performance 11–17 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Since Milton et al 10 indicated the possibility of manufacturing of auxetic composite laminates with the Poisson's ratio (PR) of À1, many researches have been focused on the development of auxetic composites and the studies of their energy absorption ability and impact resistance performance. [11][12][13][14][15][16][17] The impact resistance performance of different types of auxetic composites and auxetic structures has been assessed via both high-velocity and low-velocity impact tests by various researchers. [18][19][20][21][22][23][24] Alderson and Coenen 25 studied the low velocity impact response of different carbon fiber reinforced polymer (CFRP) laminates including conventional CFRP laminates and auxetic CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been carried out on the development of different auxetic geometries and their respective synthetic auxetic materials. [ 32–36 ] It is also reported that different auxetic geometries result in different values of NPR. Kim et al proposed a rotating polygonal prism structure, where the value of n is varied as 3, 4, and 6, which deforms by the relative rotation of the n‐gonal component prism units and gave an analytical model for predicting the Poisson's ratio of the three structures.…”
Section: Introductionmentioning
confidence: 99%